Optimization of Beta-Sitosterol Extraction from Leucaenaleucochepala by Microwave Assisted Hydrodistillation - Norlaili, Hashim; Noormazlinah, Ahmad; Mimi Sakinah, A. M.; Maria-Pilar, A. (Universiti Malaysia Pahang, 2018)
Microwave-assisted hydrodistillation (MAH) extraction process can be extract phytosterol (beta-sitosterol) from Leucaena leucochepala